Evaluation of Mantel-Haenszel Statistic for Detecting Differential Item Functioning - Abedalaziz, Nabeel (EDUCARE, 2011)
ABSTRACT: The educators have been redefining the goals of instruction and learning to include increased attention to high-level thinking skill. Mantel-Haenszel methods comprise a highly flexible methodology for assessing the degree of association between two categorical variables, whether they are nominal or ordinal, while controlling for other variables. The versatility of Mantel-Haenszel analytical approaches has made them very popular in the assessment of the DIF (Differential Item Functioning) of both dichotomous and polytomous items. The Mantel-Haenszel (M-H) procedure was originally used to Match subjects retrospectively on cancer risk factors in order to study current cancer rates (Mantel & Haenszel, 1959). The terminal objective of the study was to find out the impact of the number of score groups and the inclusion or exclusion of the studied item in forming score groups on estimating Î±s. Results indicated that: (1) fourth or more score groups yields stable Î± estimates with Mantel-Haenszel approach; and (2) the inclusion of the studied item is convergent to result in fewer items with significant chi-square values than the exclusion of the studied item in forming score groups. These findings seem to be consistent with the previous researches.KEY WORDS: Differential Item Functioning, Mantel-Haenszel method, bias, estimating, and inclusion or exclusion of the studied item.About the Author: Dr. Nabeel Abedalaziz is a Lecturer at the Department of Educational Psychology and Counseling, Faculty of Education UM (University of Malaya), 50603 Kuala Lumpur, Malaysia. He can be reached at: nabeelabdelazeez@yahoo.com and nabilaziz@um.edu.myHow to cite this article? Abedalaziz, Nabeel. (2011). âEvaluation of Mantel-Haenszel Statistic for Detecting Differential Item Functioningâ in EDUCARE: International Journal for Educational Studies, Vol.3(2) February, pp.177-186. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 22, 2010); Revised (January 25, 2011); and Published (February 17, 2011).